Tennis Sports Development at the Bengkulu Tennis School (STB) - Eka Gustari Purnama Sari; Eddy Marheni; Damrah Damrah; Anton Komaini (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
This study aims to determine organizational management, athlete training, competition programs, training programs related to tennis sports coaching at the Bengkulu Tennis School (STB). This research is qualitative research with a triangulation approach. The subjects taken in this study were 3 athlete parents, 3 coaches, and 3 administrators at the Bengkulu Tennis School (STB). The research instruments used were observation, interviews, and documentation. Based on the results of data analysis and research results show that: (1) Bengkulu Tennis School organizational managementAdequate facilities and infrastructure are available to support sports activities, and have professional trainers. (2) Athlete training starts from an early age,There are two strategies carried out by STB to recruit athletes, the first is a general strategy through social media, as well as the STB Go To School program. (3) the STB competition program has been scheduled in the program, and aims to motivate children to be enthusiastic about training, (4) The planning of the training program carried out by the STB is based on age group classification and according to the ability and needs of each athlete.